Capaian secara semantik dokumen web berasaskan domain ontologi - Arifah Che Alhadi (Universiti Kebangsaan Malaysia, 2011)
Accessing and extracting semantic information from Web documents is crucial for the realization of the semantic web and the provision of advance knowledge services. Manual extraction of semantic information is impractical and unscalable and fully automated tools are still at the very early stage to be implemented. Therefore, the use of specialized domain knowledge in the form of ontology is seen as one of the practical short terms solutions approach which be used to search and extract semantic information content from unstructured text on the web. Ontologies have been defined as "explicit representation(s) of domain", in which concepts and relationships between them are defined as a representational terms, enabling knowledge to be shared and reuse. While ontologies have been widely used to support communication and information sharing within the context of Semantic Web documents is still not thoroughly explored. The main aim of this research is therefore to propose an approach of which the unstructured nature of web documents can be semantically queried by using domain ontology.